Action research on managing the invoice age service level requirement of the invoice verification - Angola Team - Lejano, Jan Bernard F. (Animo Repository, 2021)
This action research addresses the main issue identified by the Angola Invoice Verification Team of Blue Shield Company after the researcher has noticed that their team is being slow in complying with their Service Level Agreement to handle invoices in their queue within 3 days. The issue was identified by the researcher and his two collaborators using a Fishbone diagram. The team agreed that the main reason why they are slow in reducing their invoice ages is that they are not familiar with the nature of transactions of the invoices they review. It was determined that the team uses memorization when determining the codes to be used for the invoices based on the nature of the transaction. This practice was ineffective, and the team has agreed that instead of memorizing the details for each supplier, they should be aware of how to properly assess the nature of the transactions instead. For the first cycle, the team coordinated with the Tax Team of Angola to have a training session to learn how they do the identification of the nature of transactions. The results of the training made the invoice review time improve. However, the team is still not that confident in how they review their invoice which was addressed in the second cycle by updating the tracker they use to reflect the codes per supplier as reference.